Analysis of Potential Areas of Plastic Waste Pollution Sources into the Ciliwung River Based on GIS and Multi-Criteria Decision Analysis (MCDA) - Upadana, Made Dwiyana Surya; Hafiudzan, Akmal (Indonesian Journal Publisher, 2025)
Plastic waste pollution increasingly threatens the ecological and hydrological functions of the Ciliwung River Basin, yet identifying its sources remains difficult due to interacting physical and socio-economic factors. This study aims to map potential plastic waste source areas to support upstream waste management interventions. A Geographic Information System (GIS) combined with Multi-Criteria Decision Analysis (MCDA) using a Weighted Linear Combination (WLC) approach was applied to integrate six variables: settlement typology, population density, market distribution, presence of waste facilities, distance to the river, and riverbank condition. Results show that 16.37% of the basin is classified as high-potential, 35.24% as medium, and 48.40% as low-potential. Scenario 1—emphasizing settlement typology and population density—most closely matched field observations, identifying densely populated informal settlements on disturbed riverbanks as the primary contributors to plastic waste leakage. These findings underscore the role of demographic pressure and riverbank settlement characteristics in shaping pollution risks and provide a basis for targeted interventions in high-risk areas.